Restriç\~oes macroeconômicas ao crescimento da economia brasileira: Diagnósticos e algumas proposiç\~oes de política - José Luis Oreiro; Lionello Punzo; Eliane Araújo; Gabriel Squeff (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper argues that the Brazilian economy went recently through a process of accelerated growth driven by exports and fixed capital formation. Although the pace of growth was more robust than in the 1990 decade, we can still see the presence of macroeconomic constraints to its continuation in the long run, like, an exchange rate overvaluation that has appeared in the economy in particular since 2005, and the modus operandi of its monetary policy. Such constraints may jeopardize the very sustainability of the current pace of growth in an international context that is characterized by the occurrence of an international financial crisis on a large scale and a strong global recession. Therefore, we can argue that Brazil is still in a trap made up of interest rate and exchange rate. In such contest, the elimintation of the exchange misalignment would fore a great hike in the rates of interest, which on its turn would impact negatively upon investment and thence upo the sustainbility of the economic growth in the long run. To eliminate such a trap we outline a set of policy measures, in particualr. The adoption of implicit rate of exchange targets, controls on mobility of short run capital and a flexibilizxation of the inflation targets model.
Keywords: F14; F31; F43; 330; Wirtschaftswachstum; Wirtschaftspolitik; Brasilien